PROVIDING QUALITY EDUCATION FOR SOCIAL REINTEGRATION IN NIGERIA: AN INSPIRATION FROM NATIONAL POLICY ON EDUCATION - Inuwa, Awwalu Muhammad; Bissallah, Comfort Ekele (Sokoto Educational Review, 2011)
This paper is on providing quality education for social reintegration in Nigeria: An inspiration from the national policy on education. It will not be out of place to say that Nigerian ethnic and regional tensions were magnified by socio-economic and political differences, because appropriate teaching of unity in the light of integrated resource development is presently fading away from Nigerian schools. This paper highlights on countrywide unity as contained in National Policy on Education and identifies some obstacles to unity like; economic, political, communal factors and deficiency of proper education statements. It conceptualizes quality education and quality education for national unity. Thus, the paper argues that the content and instruction should encompass an ideological free-minded intent and content, divorced from the old segmented feelings of regionalism, ethnicism and statism. It, however, recommends that; social philosophy of the national policy on education should remain a tool for national unity, NPE should introduce and stress on laws against discrimination in educational institutions. Also, education should be accessible, to every child irrespective of sex, status, tribe and regional location in Nigeria.